Structural evolution of a water oxidation catalyst by incorporation of high-valent vanadium from the electrolyte solution - Singh B.; Huang Y.-C.; Priyadarsini A.; Mannu P.; Dey S.; Lahiri G.K.; Mallik B.S.; Dong C.-L.; Indra A. (My University, 2025)
The electrochemical reconstruction of transition metal-based precatalysts during anodic water oxidation has a prominent effect on the structural, morphological, and electronic properties of the active catalysts resulting in improved oxygen evolution activity. Exploring the atomic and electronic structure of the active catalyst for electrochemical water oxidation is crucial to establish the structure-activity relationship. Herein, we have demonstrated an efficient active water oxidation catalyst, VNi-AC-1, obtained by the incorporation of high valent vanadium from the electrolyte solution during the anodic reconstruction of the precatalyst Ni-coordination polymer (CP). Though both the active catalysts Ni(O)OH and [V]-Ni(O)OH contain mixed valent Ni2+ and Ni3+ species, X-ray absorption spectroscopy reveals that the incorporation of vanadium in the active catalyst increases the amount of Ni3+ sites, shortens the Ni-O bonds, decreases the coordination number of Ni, and creates a highly disordered structure to improve the water oxidation activity. VNi-AC-1 delivered 50 mA cm−2 current density at only 290 mV overpotential compared to the hydrothermally prepared NiV-LDH (360 mV) and NiFe-LDH, (340 mV). Moreover, VNi-AC-1 recorded an excellent durability of 60 h for continuous oxygen evolution. The density functional theory calculations for the V-incorporated Ni(O)(OH) show that the O* species formation is the rate-determining step where the O-O bond formation occurred by the attack of nucleophilic hydroxide ion. © 2023 The Royal Society of Chemistry.